INVESTMENT METHODOLOGY IN PLANNING AND DEVELOPMENT OF INFRASTRUCTURE: AN UNBALANCED GROWTH APPROACH - Omoleye B. Ojuri (Journal of Construction Project Management and Innovation)
The economic as well as efficient use of scarce resources is one of the challenges in developing countries. This paper aims at providing an investment methodology to infrastructure planning and development agencies. To achieve the goal, the paper specifically analyses the unbalanced growth concept in prioritizing investment in infrastructure development. It further examines in detail the investment policies in infrastructure development in Sri-Lanka. Based on that, this paper carried out an extensive survey of the literature pertaining to available social infrastructure and the social status of Nigerian Niger Delta (ND) region. In looking for broad correlations, this paper sets aside a crucial issue - given that investment capital is scarce and living standards are low, what should get priority in terms of investment between consumption and productive activities? The study employed. An adaptation of photovoice methodology is used to collect primary data on the status of infrastructure facilities in the ND. The methodology is adopted to identify scope not captured through quantitative measures. The methodology combines photography with grassroots social action through interviews. The sample size is based on purposive sampling technique because the methodology requires adults that can participate in interview survey and handle instruments to be used for data collection. Based on that, fifty seven participants were first selected and subdivided into eight groups. The findings establish that social overhead capital (SOC) investments are more beneficial than direct productive activities (DPA) during early phase of infrastructural development and thus be given priority because the provision of SOC is relevant to addressing the appalling state of living of the people of the Nigerian ND region and thus improve the region’s human capacity. The paper concludes that the measure of self-reliance of poor people is a strong indicator of the long-term poverty reduction impact of infrastructure development. Policy recommendations and specific actionable targets are suggested.